English Workplace Toolkit (EWT) / Aisyah Nazamud-din, Lisbeth Sinan Lendik and Grecilda Augustine Tinggie - Nazamud-din, Aisyah; Lendik, Lisbeth Sinan; Tinggie, Grecilda Augustine (2020)
English Workplace Toolkit or EWT is a module designed for fresh graduates who are in search of ways to improve their command of the English language at the workplace. The objectives of this module are to improve English proficiency in key areas of job applications and interviews and apply the target language effectively for a variety of purposes in the workplace. Referring to Gagne (1965) Nine Events of Instruction, the module incorporates the instructions in each of its components. To address the needs of workplace communication, all materials were formulated to be manageable by novice users and incorporated beginners to intermediate English language competencies. This module place emphasis on the use of English language suitable to the Malaysian context. EWT can be accessed through its website designed with a user-friendly interface. Users of EWT can use the module independently through selfdirected learning or used by language instructors as an aid in their teaching delivery.